Fluorescence quenching and time-resolved fluorescence studies of alpha-Mannosidase from Aspergillus fischeri (NCIM 508) - Shashidhara, K. S.; Gaikwad, Sushama M. (Journal of Fluorescence, 2007)
Apart from the vital role in glycoprotein biosynthesis and degradation, alpha-mannosidase is currently an important therapeutic target for the development of anticancer agents. Fluorescence quenching and time-resolved fluorescence of alpha-mannosidase, a multitryptophan protein from Aspergillus fischeri were carried out to investigate the tryptophan environment. The tryptophans were found to be differentially exposed to the solvent and were not fully accessible to the neutral quencher indicating heterogeneity in the environment. Quenching of the fluorescence by acrylamide was collisional. Surface tryptophans were found to have predominantly positively charged amino acids around them and differentially accessible to the ionic quenchers. Denaturation led to more exposure of tryptophans to the solvent and consequently in the significant increase in quenching with all the quenchers. The native enzyme showed two different lifetimes, tau (1) (1.51 ns) and tau (2) (5.99 ns). The average lifetime of the native protein (tau) (3.187 ns) was not affected much after denaturation (tau) (3.219 ns), while average lifetime of the quenched protein samples was drastically reduced (1.995 ns for acrylamide and 1.537 ns for iodide). This is an attempt towards the conformational studies of alpha-mannosidase.
Keywords: alpha-Mannosidase; Denaturation; fluorescence; lifetime; Solute quenching

Functional and conformational transitions of mevalonate diphosphate decarboxylase from Bacopa monniera - Shakeel, Abbassi; Patel, Krunal; Khan, Bashir Mohammad; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of mevalonate diphosphate decarboxylase (MDD), a key enzyme of mevalonate pathway in isoprenoid biosynthesis, from Bacopa monniera (BmMDD), cloned and overexpressed in Escherichia coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and Circular dichroism spectroscopy. Native BmMDD is a helix dominant structure with 45% helix and 11% sheets and possesses seven tryptophan residues with two residues exposed on surface, three residues partially exposed and two situated in the interior of the protein. Thermal denaturation of BmMDD causes rapid structural transitions at and above 40 degrees C and transient exposure of hydrophobic residues at 50 degrees C, leading to aggregation of the protein. An acid induced molten globule like structure was observed at pH 4, exhibiting altered but compact secondary structure, distorted tertiary structure and exposed hydrophobic residues. The molten globule displayed different response at higher temperature and similar response to chemical denaturation as compared to the native protein. The surface tryptophans have predominantly positively charged amino acids around them, as indicated by higher K-SV for IC as compared to that for CsCl. The native enzyme displayed two different lifetimes, vi (1.203 +/- 0.036 ns) and tau 2 (3.473 +/- 0.12 ns) indicating two populations of tryptophan. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggregation; CD spectroscopy; Fluorescence quenching; Mevalonate diphosphate decarboxylase; Unfolding

Functional stability and structural transitions of kallikrein: spectroscopic and molecular dynamics studies - Dalal, Sayli; Mhashal, Anil; Kadoo, Narendra; Gaikwad, Sushama M. (Journal of Biomolecular Structure & Dynamics, 2017)
Kallikrein, a physiologically vital serine protease, was investigated for its functional and conformational transitions during chemical (organic solvents, Gdn-HCl), thermal, and pH induced denaturation using biochemical and biophysical techniques and molecular dynamics (MD) simulations approach. The enzyme was exceptionally stable in isopropanol and ethanol showing 110% and 75% activity, respectively, after 96h, showed moderate tolerance in acetonitrile (45% activity after 72h) and much lower stability in methanol (40% activity after 24h) (all the solvents [90% v/v]). Far UV CD and fluorescence spectra indicated apparent reduction in compactness of KLKp structure in isopropanol system. MD simulation studies of the enzyme in isopropanol revealed (1) minimal deviation of the structure from native state (2) marginal increase in radius of gyration and solvent accessible surface area (SASA) of the protein and the active site, and (3) loss of density barrier at the active site possibly leading to increased accessibility of substrate to catalytic triad as compared to methanol and acetonitrile. Although kallikrein was structurally stable up to 90 degrees C as indicated by secondary structure monitoring, it was functionally stable only up to 45 degrees C, implicating thermolabile active site geometry. In GdnHCl [1.0M], 75% of the activity of KLKp was retained after incubation for 4h, indicating its denaturant tolerance. A molten globule-like structure of KLKp formed at pH 1.0 was more thermostable and exhibited interesting structural transitions in organic solvents. The above results provide deeper understanding of functional and structural stability of the serine proteases at molecular level.
Keywords: isopropanol tolerance; Kallikrein; MD Simulation; Molten globule; Serine protease; Thermostability